HRV and blood parameters for assessing the physiological functioning of cyclists during long-distance rides across different altitudes - Du, W.; Zhang, M.; Niu, X.; Li, H.; Wan, Y. (Frontiers in Physiology, 2025)
Objective: This study aimed to systematically investigate the changes and interrelationships between heart rate variability (HRV) and hematological parameters in cyclists during prolonged exposure to varying altitudes, in order to reveal the dynamic interplay between autonomic nervous system regulation and hematological adaptation.